The design of the building envelope between innovation and experimentation - Claudi de Saint Mihiel, Alessandro (TECHNE - Journal of Technology for Architecture and Environment, 2020)
Peter Galison, philosopher of science, says that surfaces are not as we often describe them, that is, membranes that enclose spaces. The surfaces are active and highly structured parts, with a degree of complexity that allows them to size and order the matter, alter the optics or become biologically active. Actual technological developments, along with science innovation, refer to new meanings of the concept of surface, in terms of the interface between two “environments” brought into contact, in which forms of energy and information exchange take place. This new notion applied to transparent surfaces manifests the level of contamination in progress: the “limit surface” favours osmosis, interaction and communication processes in the environments it interfaces. The delimitation of space becomes commutation, and the once rigid separation, thanks to the new soft and hard technologies, turns into the possibility of transition of a continuous exchange activity. The appearance of the façades and surfaces hides a secret transparency, a thickness without thickness, an imperceptible quantity. The Construction procedures evolution and the use of advanced technologies for transparent envelopes or partitions and of IT systems for the management of building performance, have allowed a profound change of view in the conception of the project and of its realisation, producing manufactured products that interact with the environment and adapt themselves according to material and immaterial flows. In many cases, the transparent envelope, thanks to innovative solutions, interacts with external environmental flows (air, light, solar radiation, etc.), contributing to the improvement of the general conditions of users’ well-being. Thus, technological innovation applied to the envelopes or to other parts of the buildings, gives a picture of the transformations taking place in the design solutions for glass surfaces, intended as a sensitive and selective interface with the environment. The evolution process of the building envelope shows how the trend is towards systems with a greater adaptability to the variation of external climatic conditions. In this regard, adaptive façades can react to stimuli or external forces in many different ways: they can in fact modify shape and geometry, color, transparency, permeability, etc. The link between the façades of complex buildings and the energy produced from renewable sources is often essential, also with reference to the achievement of the ever closer zero energy goal. In this perspective, the Smartwall project identifies an original line of work in the project of innovative façade components for the building industry, through which the industrial partners involved benefited from university research by initiating virtuous processes of technological innovation, opening up to new sectors of the market and focusing on new production chains. Experimental and applied research was conducted thanks to a competitive call POR Calabria 2014/2020 for Axis 1 - “Promotion of research and innovation”; Specific objective 1.1 “Increasing business innovation activity”. The project covered the entire industrial development process aimed at creating a prototype of an external door frame profile. The system is based on the integration of traditional components and mechanics with intelligent systems technologies aimed at ensuring high levels of indoor comfort with reduced energy consumption. The contribution of architecture research and technological design refers to some methodological and operational issues in the relationship established between the many dimensions of innovation and the architectural project. On the one hand we find the themes of environmental design, in which the conception of the habitat is not limited only to the physical-formal aspects, but also to the intangible determinations of the project, oriented towards an idea of ​​environmental governance; on the other hand, the complex problems of innovative techniques and materials are identified, as well as the processes, methodologies, procedures and topics for the sustainable project, developed according to the project implications and the necessary methods of its technical control. In light of these considerations, we can state that the activities and perspectives of research and design experimentation outlined in the following contribution, referring to the different cultural, innovation and sustainability dimensions of the project, can offer concrete answers in theoretical and practical terms to the current and future challenges, proceeding towards a vision of the project increasingly detached from technical specializations and brought back to its centrality, thus responding significantly to issues such as energy efficiency and saving. L’apparenza delle facciate e delle superfici nasconde una trasparenza segreta, uno spessore senza spessore, una quantità impercettibile. L’evoluzione dei procedimenti costruttivi e l’utilizzo di tecnologie avanzate per chiusure o partizioni trasparenti e dei sistemi informatici per la gestione delle prestazioni degli edifici, hanno consentito un profondo cambiamento di visuale nella concezione del progetto e della sua realizzazione, producendo manufatti che interagiscono con l’ambiente e che si conformano tenendo conto dei flussi materiali ed immateriali. In molti casi l’involucro trasparente, grazie a soluzioni innovative interagisce con i flussi ambientali esterni (aria, luce, irraggiamento solare, ecc.), contribuendo al miglioramento delle generali condizioni di benessere degli utenti. L’innovazione tecnologica applicata quindi agli involucri o, in maniera meno spinta ad altre parti degli edifici, restituisce un quadro delle trasformazioni in atto nelle soluzioni progettuali per le superfici vetrate, intese come un’interfaccia sensibile e selettiva con l’ambiente. Il processo di evoluzione dell’involucro degli edifici mostra come la tendenza sia rivolta verso sistemi con maggiore adattività verso la variazione delle condizioni climatiche esterne. A tal riguardo, il modo con cui una facciata adattiva può reagire a degli stimoli o a delle forzanti esterne sono molteplici: esse possono infatti modificare forma e geometria, colore, trasparenza, permeabilità, etc. Il legame tra facciate di edifici complessi ed energia prodotta da fonti di energia rinnovabili è spesso imprescindibile, anche con riferimento al raggiungimento del sempre più prossimo obiettivo “zero energy”. In quest’ottica, il progetto, Smartwall individua una linea di lavoro originale attraverso il progetto di componenti innovativi di facciata per l’edilizia attraverso il quale i partner industriali coinvolti hanno beneficiato della ricerca universitaria avviando processi virtuosi di innovazione tecnologica, aprendosi a nuovi settori del mercato e puntando su nuove produzioni. La ricerca sperimentale e applicata è stata condotta grazie a un bando competitivo POR Calabria 2014/2020 per l’Asse 1 - “Promozione della ricerca e dell’innovazione”; Obiettivo specifico 1.1 “Incremento dell’attività di innovazione delle imprese” e ha riguardato l’intero iter di sviluppo industriale finalizzato alla realizzazione di un prototipo di profilo di serramento esterno. Il sistema è basato sull’integrazione della tradizionale componentistica e meccanica con le tecnologie degli intelligent systems finalizzate ad assicurare alti livelli di comfort indoor con ridotti consumi energetici. Il contributo della ricerca e della progettazione tecnologica dell’architettura è riferito ad alcune questioni metodologiche e operative nel rapporto che si istituisce fra le molte dimensioni dell’innovazione e il progetto di architettura. Da un lato si rinvengono le tematiche della progettazione ambientale in cui la concezione dell’habitat non è limitata ai soli aspetti fisico-formali, ma anche alle determinazioni immateriali del progetto e orientata a un’idea di governance ambientale; dall’altro, si individuano le complesse problematiche delle tecniche e dei materiali innovativi oltre che dei processi, delle metodologie, delle procedure e dei topics per il progetto sostenibile, sviluppate secondo le implicazioni sul progetto e le necessarie modalità del suo controllo tecnico. Alla luce delle considerazione fatte si può affermare che le attività e le prospettive di ricerca e sperimentazione progettuale delineate nel contributo che segue, riferite alle diverse dimensioni culturali, di innovazione, di sostenibilità del progetto, possano offrire risposte concrete in termini teorici e applicativi alle sfide in atto e a quelle future, procedendo verso una visione del progetto sempre più sganciata dagli specialismi tecnicistici e ricondotta verso la sua centralità, contribuendo in modo significativo a rispondere a tematiche quali l’efficienza e il risparmio energetico.